Motivational Aspects of Using Computers for Writing among the Malaysian ESL Students - Abdul Haim, Huzaina; Mahmood, Foziah; Ghani, Munirah Mohd; Rajindra, Sarasvati (Advances in Social Sciences Research Journal, 2014)
Past research have shown that students view activities using computers in language learning to be highly motivating (Krendl, 1988). A more recent study conducted by Warschauer (1996), especially focusing on ESL and EFL students’ writing in universities in Hong Kong, Taiwan and the US, has found encouraging results with regards to students’ motivational attitude towards using computers in writing. In the Malaysian context however, very few researches have been conducted to study the use of computers in language learning at the tertiary level, particularly in identifying factors that affect students’ motivation in learning writing using computers. A 42 question survey investigating the attitude of Malaysian students was administered and it was found that students were highly motivated and felt empowered to study language and writing via the computer.